1994
DOI: 10.1029/94jc01171
|View full text |Cite
|
Sign up to set email alerts
|

GPS precise tracking of TOPEX/POSEIDON: Results and implications

Abstract: A reduced dynamic filtering strategy that exploits the unique geometric strength of the Global Positioning System(GPS) to minimize the effects of force model errors has yielded orbit solutions for TOPEX/POSEIDON which appear accurate to better than 3 cm (1 σ) in the radial component. Reduction of force model error also reduces the geographic correlation of the orbit error. With a traditional dynamic approach, GPS yields radial orbit accuracies of 4–5 cm, comparable to the accuracy delivered by satellite laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(49 citation statements)
references
References 26 publications
1
44
0
2
Order By: Relevance
“…Data from the GPS system on T/P supported radial RMS orbit accuracies better than 3 cm soon after launch [Bertiger et al, 1994]. The GPSDR did not use codeless tracking techniques, and the most accurate (ionosphere-free) observables could be formed only when the GPS antispoofing (AS) function was turned off.…”
Section: Antenna Phase Variations From Topex/poseidon and Gracementioning
confidence: 99%
See 1 more Smart Citation
“…Data from the GPS system on T/P supported radial RMS orbit accuracies better than 3 cm soon after launch [Bertiger et al, 1994]. The GPSDR did not use codeless tracking techniques, and the most accurate (ionosphere-free) observables could be formed only when the GPS antispoofing (AS) function was turned off.…”
Section: Antenna Phase Variations From Topex/poseidon and Gracementioning
confidence: 99%
“…Early GRACE-based calibrations of the GPS transmitters practically eliminated a long-unexplained error in the realization of GPS measurements from the TOPEX/Poseidon (T/P) altimeter mission. In particular, a 6 cm anomaly in the solved-for height of the T/P GPS antenna boom [Bertiger et al, 1994] was reduced to insignificance [Haines et al, 2006]. Similar GRACE-based calibrations significantly stabilized the scale of the TRF realized from GPS alone [Haines et al, 2007], while updated LEO-based antenna calibrations have shown promise for determining the complete TRF, including the origin as well as scale [e.g., Haines et al, 2007;Desai et al, 2008;Haines et al, 2011;Weiss et al, 2013].…”
Section: Using Orbiting Antennas As Referencesmentioning
confidence: 99%
“…The first extensive use of the GPS for LEO POD was made by the TOPEX/Poseidon altimeter mission to determine the ocean topography (Fu et al 1994). The analysis of continuously collected GPS carrier phase observations allowed for an orbit determination with an accuracy of better than 3 cm in the radial direction (Bertiger et al 1994). Since that time the quality of GPSderived LEO trajectories has steadily improved thanks to numerous improvements in the GPS orbit and clock products provided by the International GNSS Service (IGS, Dow et al 2005), in the dynamic background models (Flechtner et al 2006), and in modeling the carrier phase observations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the radiation force, at GPS altitude, is only second in magnitude to the gravitational pull from the Sun, Earth and Moon, its uncertainties are much higher (Table 1). The solar radiation model has received relatively little attention since the publication of the T20 model by Fliegel et al (1992) and is considered to be the largest error source in GPS orbit determination (Bertiger et. al.…”
Section: Introductionmentioning
confidence: 99%